Prevalence and Distribution of Listeria monocytogenes in Three Commercial Tree Fruit Packinghouses - Simonetti, Tobin; Peter, Kari; Chen, Yi; Jin, Qing; Zhang, Guodong; LaBorde, Luke F.; Macarisin, Dumitru (Frontiers in Microbiology, 2021)
A two-year longitudinal study of three tree fruit packinghouses was conducted to determine the prevalence and distribution of Listeria monocytogenes. Samples were collected from 40 standardized non-food-contact surface locations six different times over two 11-month production seasons. Of the 1437 samples collected, the overall prevalence of L. monocytogenes over the course of the study was 17.5%. Overall prevalence did not differ significantly (p > 0.05) between each year. However, values varied significantly (p<0.05) within each production season following packing activity levels; increasing in the fall, peaking in early winter, and then decreasing through spring. L. monocytogenes was most often found in the packing line areas where moisture and fruit debris were commonly observed and less often in dry cold storage and packaging areas. Persistent contamination was attributed to inability of water drainage systems to prevent moisture accumulation on floors and equipment during peak production times, and uncontrolled employee and equipment traffic throughout the facility. This is the first multi-year longitudinal surveillance study to compare L. monocytogenes prevalence at standardized sample sites common to multiple tree fruit packinghouses. Recommendations based on our results will help packinghouse operators to identify critical areas for inclusion in their L. monocytogenes environmental monitoring programs.